(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The study investigated the effects of ethnoscience-based and traditional laboratory practical teaching strategies on science process skills acquisition of secondary school Biology students in Nigeria. Quasi-experiment of non-equivalent control group design was used. Three coeducational schools out of seventeen of such in Nsukka local government area of Enugu State, Nigeria were purposively selected. An intact class in each of the three schools was assigned randomly to 2 experimental groups taught using ethnoscience and traditional laboratory practical and a control group taught using expository. One hundred and fifty Senior Secondary two students formed the sample. Twenty item Test Of Science Process Skills Acquisition validated by experts in Science Education was the instrument for data collection. Research questions were answered using Mean and Standard Deviation. Analysis of Covariance was used for testing hypotheses. Findings reveal that ethnoscience-based students performed better than traditional practical group. It was recommended that teachers should provide instructional activities from students’ environment. That will challenge them to be actively involved in classroom.